2013
DOI: 10.1371/journal.pone.0066500
|View full text |Cite
|
Sign up to set email alerts
|

Stress Impact on Resting State Brain Networks

Abstract: Resting state brain networks (RSNs) are spatially distributed large-scale networks, evidenced by resting state functional magnetic resonance imaging (fMRI) studies. Importantly, RSNs are implicated in several relevant brain functions and present abnormal functional patterns in many neuropsychiatric disorders, for which stress exposure is an established risk factor. Yet, so far, little is known about the effect of stress in the architecture of RSNs, both in resting state conditions or during shift to task perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 72 publications
9
100
1
2
Order By: Relevance
“…Further investigation of chronic stress, including early life stress, on the DMN will do much to enrich our understanding of changes to large-scale intrinsic connectivity networks. Interestingly, although there are some studies that suggests stress decreases connectivity in the DMN, an animal study [28] and a study of medical students [29] found that exposure to prolonged stress was related to increased DMN activity. Of note, Kennis et al [30] recently showed reduced resting state connectivity between the perigenual ACC (as part of the mPFC and DMN) and the superior medial frontal gyrus and medial temporal gyrus in traumatizes subjects with and without PTSD, relative to controls, consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of chronic stress, including early life stress, on the DMN will do much to enrich our understanding of changes to large-scale intrinsic connectivity networks. Interestingly, although there are some studies that suggests stress decreases connectivity in the DMN, an animal study [28] and a study of medical students [29] found that exposure to prolonged stress was related to increased DMN activity. Of note, Kennis et al [30] recently showed reduced resting state connectivity between the perigenual ACC (as part of the mPFC and DMN) and the superior medial frontal gyrus and medial temporal gyrus in traumatizes subjects with and without PTSD, relative to controls, consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These lines of evidence, combined with our current observations, support an explanation that increased fasting PG and insulin levels (i.e., greater insulin resistance) causes a reduction of functional connectivity in the DMN, leading to reduced uptake of 18 F-FDG (i.e., glucose hypometabolism), especially in the precuneus. Furthermore, prolonged stress can affect the pattern of activity in the DMN (27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous multimodal neuroimaging studies have shed light on this functionstructure association, underlining cognition, aging, disease, and behavior. 49 The changed activity within the DMN in response to chronic stress exposure has been found in humans 50 and animals. 51 The impairment of cortical structures in HA Tibetans is likely to reflect the stress-induced atrophic effects in cortical regions.…”
Section: Implications For the Changes In Cortical Structural Measuremmentioning
confidence: 99%